Identification of a lipoteichoic acid glycosyltransferase enzyme reveals that GW-domain containing proteins can be retained in the cell wall of Listeria monocytogenes in the absence of lipoteichoic acid or its modifications - Percy,M; Karinou,E; Webb,A; Grundling,A (Journal of Bacteriology, 2016)
Listeria monocytogenes is a food-borne Gram-positive bacterial pathogen and many of its virulence factors are either secreted proteins, or proteins covalently or non-covalently-attached to the cell wall. Previous work has indicated that non-covalently-attached proteins with GW domains are retained in the cell wall by binding to the cell wall polymer lipoteichoic acid (LTA). LTA is a glycerolphosphate polymer, which is modified in L. monocytogenes with galactose and D-alanine residues. We identified Lmo0933 as the cytoplasmic glycosyltransferase required for the LTA glycosylation process and renamed the protein GtlA for glycosyltransferase LTA A. Using L. monocytogenes mutants lacking galactose or D-alanine modifications or the complete LTA polymer, we show that GW-domain proteins are still retained within the cell wall, indicating that other cell wall polymers are involved in the retention of GW-domain proteins. Further experiments reveal peptidoglycan as the binding receptor as a purified GW domainfusion protein can bind to L. monocytogenes cells lacking wall teichoic acid (WTA) as well as purified peptidoglycan derived from a wild-type or WTA-negative strain. With this, we not only identified the first enzyme involved in the LTA glycosylation process, but we also provide new insight into the binding mechanism of non-covalently attached cell wall proteins.